2000
DOI: 10.1046/j.1365-2702.2000.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

‘You do know he’s had a stroke, don’t you?’ Preparation for family care‐giving – the neglected dimension

Abstract: Countries throughout the developed world have introduced a policy of community care for older people to reduce costs to the state and maintain quality of life. In reality community care is largely family care and recognition of the need to support family carers is being promoted through the notion of partnership with professional carers. Such a partnership calls for a more complete understanding of how carers' needs change over time and how professional support can be most effective. Support is particularly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
107
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 23 publications
(22 reference statements)
15
107
0
1
Order By: Relevance
“…Caregivers are often anxious and express concern for their family member's immediate survival. This phase is consistent with caregivers desire to understand ''What's it all about'' [41].…”
Section: Phase One: Event/diagnosissupporting
confidence: 60%
See 1 more Smart Citation
“…Caregivers are often anxious and express concern for their family member's immediate survival. This phase is consistent with caregivers desire to understand ''What's it all about'' [41].…”
Section: Phase One: Event/diagnosissupporting
confidence: 60%
“…Although there are numerous studies describing caregivers support needs, only a small number of studies made specific reference to the time in the illness trajectory that these needs occurred. Therefore, we used primarily 11 studies in combination with the clinical course for stroke to inform the TIR framework [28,[39][40][41][42][43][44][45][46][47][48].…”
Section: ''Timing It Right'' Frameworkmentioning
confidence: 99%
“…In a qualitative study, 28 which followed family caregivers over an 18-month period, the caregivers reported that caregiving became more routine and that their expertise and competence grew over time. Depressive symptoms are common among patients and spouses in the early stages after stroke.…”
Section: Course Of Psychosocial Functioningmentioning
confidence: 99%
“…87 The specific needs for support identified by carers include information about the long-term implications of stroke and the availability of community services. 90,92,94,98 Reported solutions suggested by carers include access to advisers, opportunity for regular reassessments of the patient, improved access to day care and respite care, carer support groups, and access to emergency calls for support. 94 Simon and Kumar (2002) reported that caregivers felt that they were not adequately consulted and considered by professionals.…”
Section: Mckevitt Et Al Qualitative Studies Of Stroke: a Systematic Rmentioning
confidence: 99%